Analysis of Influencer Jonathan Liandi's Online Identity on YouTube Media: Analisis Identitas Online Influencer Jonathan Liandi pada Media YouTube - Dicky, Muhammad (Procedia of Social Sciences and Humanities, 2025)
Jonathan Liandi is one of the successful examples of influencers who have managed to build a strong online identity in the world of e-sports. He is not only known for his expertise in playing games, but also for his charismatic communication skills and consistent persona across various social media platforms. YouTube is one of the media used to build his personal branding. His popularity did not happen instantly, but rather through a long process involving various careful communication and branding strategies. This study analyzes the formation of the online identity and online authenticity of Jonathan Liandi, a leading content creator in the Indonesian esports community. Through an analysis of his YouTube channel, content strategy, and interaction with the audience, this study reveals how Jonathan's online identity is formed from his professional background as a former Mobile Legends player and his sincere communication style. Consistency in narrative, reflection of real personality, and active engagement with the audience create trust and loyalty from his followers. This study concludes that authenticity, relevance, and content quality are key elements in building a strong online presence and maintaining audience engagement. Highlights: Authenticity & Consistency – Jonathan Liandi maintains a genuine persona, reflecting his real personality and professional background to build trust and loyalty. Content Strategy & Engagement – His success stems from a well-planned YouTube content strategy, including interactive formats that actively engage his audience. Strong Personal Branding – By leveraging his expertise as a former Mobile Legends player and charismatic communication style, he establishes a distinct and influential online identity. Keywords: Online Identity, Jonathan Liandi, Context Collapse, YouTube